2021
DOI: 10.1038/s41467-021-23816-3
|View full text |Cite
|
Sign up to set email alerts
|

ERRγ enhances cardiac maturation with T-tubule formation in human iPSC-derived cardiomyocytes

Abstract: One of the earliest maturation steps in cardiomyocytes (CMs) is the sarcomere protein isoform switch between TNNI1 and TNNI3 (fetal and neonatal/adult troponin I). Here, we generate human induced pluripotent stem cells (hiPSCs) carrying a TNNI1EmGFP and TNNI3mCherry double reporter to monitor and isolate mature sub-populations during cardiac differentiation. Extensive drug screening identifies two compounds, an estrogen-related receptor gamma (ERRγ) agonist and an S-phase kinase-associated protein 2 inhibitor,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 36 publications
2
35
0
Order By: Relevance
“…In addition to these factors, Sakamoto et al demonstrated that ERR signaling plays an essential role in postnatal cardiac maturation in mice (Sakamoto et al 2020 ). Coincident with this finding, we recently reported that an ERRγ agonist enhanced maturation with T-tube formation in iPSC cardiomyocytes in vitro (Miki et al 2021 ). Garbern et al demonstrated that the inhibition of mTOR signaling, which acts as a nutrient sensor and a cell cycle regulator, by a small compound, Torin 1, enhanced the maturation of iPSC cardiomyocytes via p53-induced quiescence (Garbern et al 2020 ).…”
Section: Recent Progresses On Quality Of Ipsc-derived Cells For Disease Study and Treatmentsupporting
confidence: 62%
“…In addition to these factors, Sakamoto et al demonstrated that ERR signaling plays an essential role in postnatal cardiac maturation in mice (Sakamoto et al 2020 ). Coincident with this finding, we recently reported that an ERRγ agonist enhanced maturation with T-tube formation in iPSC cardiomyocytes in vitro (Miki et al 2021 ). Garbern et al demonstrated that the inhibition of mTOR signaling, which acts as a nutrient sensor and a cell cycle regulator, by a small compound, Torin 1, enhanced the maturation of iPSC cardiomyocytes via p53-induced quiescence (Garbern et al 2020 ).…”
Section: Recent Progresses On Quality Of Ipsc-derived Cells For Disease Study and Treatmentsupporting
confidence: 62%
“…For example, an hiPSC-CM engineered heart model exibited increased expression of ESRRA and PPARGC1A 51 . In addition, an ERRγ agonist was recently identified as an inducer to drive hiPSC-CM maturation in an unbiased screen using a TNNI3 reporter hiPSC line 52 . These collective results suggest that strategies aimed at activation of ERR signaling may enhance cardiomyocyte maturation in culture and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an estrogen-related receptor gamma agonist was shown to induce hiPSC-CMs to promote maturation in terms of cardiac gene expression, morphology, and function. 49,50 Overall, these findings underscore the importance of metabolism and the need to optimize culture conditions to promote the maturation of hiPSC-CMs (Fig. 3).…”
Section: Metabolism Of Hipsc-cmsmentioning
confidence: 67%